The Effect of Using DRTA (Directed Reading Thinking Activity) Strategy on Reading Comprehension of Grade 11 Students at SMK SW Persiapan Pematang Siantar - Situmorang, Dwira May; Sinurat, Bloner; Sihombing, Partohap S. R. (International Journal Corner of Educational Research, 2023)
This research seeks to determine the effectiveness of implementing the Directed Reading Thinking Activity (DRTA) strategy in enhancing the reading comprehension abilities of Grade 11 students at SMK SW Persiapan Pematang Siantar during the academic year 2022/2023. The study utilized a quantitative research approach with a quasi-experiment design. The dependent variable is the student's reading comprehension ability, while the independent variable is the DRTA strategy. The research subjects were Grade 11 students at SMK SW Persiapan Pematang Siantar during the academic year 2022/2023. The study's objective is to evaluate the effectiveness of the DRTA strategy on reading comprehension. The study utilized pre-test and post-test instruments, and the results indicated that the mean score of the experimental group was higher than the control group. Therefore, it can be deduced that implementing the DRTA strategy positively influences the reading comprehension ability of Grade 11 students at SMK SW Persiapan Pematang Siantar during the academic year 2022/2023.